Teaching Critical Thinking Skills Using Case-Based Method: A Case Study in Critical Reading and Writing Course - Yulhenli Thabran; Nunung Fajaryani; Mukhlas Abrar (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
The following research examined the experiences and perspectives of five students who took a case-based critical reading and writing course. Many university students in Indonesia lack critical thinking skills due to our learning system, which places little emphasis on critical reasoning in assessing and solving problems. They are used to be taught to memorize information rather than examining, analyzing, and solving problems. In this regard, we designed a case study to examine our students' perceptions of the difficulties associated with case-based learning and their strategies for resolving the issues as they moved throughout their case-based learning. We chose five students who had taken the course and collected data from them to learn about their experiences and perspectives. We gathered information about their experiences through observation, note-taking, a survey, an analysis of their writing, and an in-depth interview. Our findings indicated that the students encountered difficulties working in groups, identifying appropriate cases and resolving them, and writing critical commentary for reflective writing. However, as the lectures continued, they overcame their difficulties by developing a collaborative spirit throughout the course, mastering the art of case construction, and paying close attention to their grammar when completing their writing assignments.